Pharmacokinetic profile of defibrotide in patients with renal impairment - Tocchetti P; Tudone E; Marier JF; Marbury TC; Zomorodi K; Eller M (Dove Medical Press, 2016)
Paola Tocchetti,1 Elena Tudone,2 Jean-Francois Marier,3 Thomas C Marbury,4 Katie Zomorodi,5 Mark Eller6 1Gentium, 2Clinical Operations, Gentium, Villa Guardia, Como, Italy; 3Reporting and Analysis Services, Pharsight, a Certara Company, Montreal, Quebec, Canada; 4Orlando Clinical Research Center, Orlando, FL, 5Early Development and Clinical Pharmacology, Jazz Pharmaceuticals, 6Early Drug Development, Jazz Pharmaceuticals, Palo Alto, CA, USA Abstract: Hepatic veno-occlusive disease, also called sinusoidal obstruction syndrome (VOD/SOS), is an unpredictable, potentially life-threatening complication of hematopoietic stem cell transplant conditioning. Severe VOD/SOS, generally associated with multiorgan dysfunction (pulmonary or renal dysfunction), may be associated with >80% mortality. Defibrotide, recently approved in the US, has demonstrated efficacy treating hepatic VOD/SOS with multiorgan dysfunction. Because renal impairment is prevalent in patients with VOD/SOS, this Phase I, open-label, two-part study in adults examined the effects of hemodialysis and severe or end-stage renal disease (ESRD) on defibrotide pharmacokinetics (PK). Part 1 compared defibrotide PK during single 6.25 mg/kg doses infused with and without dialysis. Part 2 assessed defibrotide plasma PK after multiple 6.25 mg/kg doses in nondialysis-dependent subjects with severe/ESRD versus healthy matching subjects. Among six subjects enrolled in Part 1, percent ratios of least-squares mean and 90% confidence intervals (CIs) on dialysis and nondialysis days were 109.71 (CI: 97.23, 123.78) for maximum observed plasma concentration (Cmax); 108.39 (CI: 97.85, 120.07) for area under the concentration–time curve to the time of the last quantifiable plasma concentration (AUC0–t); and 109.98 (CI: 99.39, 121.70) for AUC extrapolated to infinity (AUC0–∞). These ranges were within 80%–125%, indicating no significant effect of dialysis on defibrotide exposure/clearance. In Part 2, defibrotide exposure parameters in six subjects with severe/ESRD after multiple doses (AUC0–t, 113 µg·h/mL; AUC over dosing interval, 113 µg·h/mL; Cmax, 53.8 µg/mL) were within 5%–8% of parameters after the first dose (AUC0–t, 117 µg·h/mL; AUC0–∞, 118 µg·h/mL; Cmax, 54.9 µg/mL), indicating no accumulation. Defibrotide peak and extent of exposures in those with severe/ESRD were ~35%–37% and 50%–60% higher, respectively, versus controls, following single and multiple doses. One adverse event (vomiting, possibly drug-related) was reported. These findings support defibrotide prescribing guidance stating no dose adjustment is necessary for hemodialysis or severe/ESRD. Keywords: dialysis, end-stage renal disease, hepatic veno-occlusive disease, sinusoidal obstruction syndrome